Halal Tourism Policy in the Contemporary Era: A Maqāṣid al-Sharīʿah Perspective on Regulatory Gaps - Farid Wajdi; Rizki Firmanda Dardin; Ummi Salamah; Mhd Nurhusein Daulay; Kholidah (MILRev: Metro Islamic Law Review, 2026)
This study examines the implementation of halal tourism policies in Indonesia in the contemporary era, which has developed amid regulatory fragmentation and regional-level differences in interpretation, due to the absence of a comprehensive national legal umbrella. Halal tourism is not placed solely as an economic and branding instrument, but as a public legal policy issue related to legal certainty, normative authority, and the achievement of benefits. This research employs normative legal methods, including legislative and conceptual approaches. The analysis was carried out qualitatively through doctrinal interpretation and critical legal reasoning of laws and regulations, regional policies, DSN-MUI fatwas, and relevant academic literature. The results of the study show that the absence of national regulations has given rise to a plurality of halal tourism policy models, ranging from the binding formalisation of Sharia in Aceh, a pragmatic market-based approach in West Nusa Tenggara, to the rejection of halal terminology in Bali, based on the protection of cultural identity. In this context, the DSN-MUI fatwa functions as a normative and ethical authority that is a soft law without juridical binding, so it has not been able to guarantee the consistency of halal tourism governance nationally. An evaluation based on maqasid shari'ah, especially the protection of religion, intellect, and property, shows that halal tourism policies across regions still tend to be symbolic and pragmatic and have not fully realized the benefits or increased the utility of tourists in worldly and ukhrawi (falah) ways. This study concludes that a national policy framework for halal tourism is needed, based on adaptive, inclusive minimum national standards that ensure legal certainty while respecting the plurality of regional cultures. The academic contribution of this research lies in the formulation of a halal tourism legal framework based on maqasid shari'ah that integrates Islamic normative values with the principles of decentralisation and pluralism of Indonesian law.